Computer-aided diagnosis of cervical dysplasia using colposcopic images - Ma, Jing-Hang; You, Shang-Feng; Xue, Ji-Sen; Li, Xiao-Lin; Chen, Yi-Yao; Hu, Yan; Feng, Zhen (Frontiers in Oncology, 2022)
Background: computer-aided diagnosis of medical images is becoming more significant in intelligent medicine. Colposcopy-guided biopsy with pathological diagnosis is the gold standard in diagnosing CIN and invasive cervical cancer. However, it struggles with its low sensitivity in differentiating cancer/HSIL from LSIL/normal, particularly in areas with a lack of skilled colposcopists and access to adequate medical resources. Methods: the model used the auto-segmented colposcopic images to extract color and texture features using the T-test method. It then augmented minority data using the SMOTE method to balance the skewed class distribution. Finally, it used an RBF-SVM to generate a preliminary output. The result, integrating the TCT, HPV tests and age, were combined into a Naive Bayes classifier for cervical lesion diagnosis. Results: the multi-modal machine learning model achieved physician-level performance (sensitivity: 51.2%, specificity: 86.9%, accuracy: 81.8%) and it could be interpreted by feature extraction and visualization. With the aid of the model, colposcopists improved the sensitivity from 53.7% to 70.7% with an acceptable specificity of 81.1% and accuracy of 79.6%. Conclusion: using a computer-aided diagnosis system, physicians could identify cancer/HSIL with greater sensitivity, which guided biopsy to take timely treatment.